2022
DOI: 10.1038/s41419-022-05080-5
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic myeloid-derived suppressive cells mitigate over-adipogenesis of bone marrow microenvironment in aplastic anemia by inhibiting CD8+ T cells

Abstract: Aplastic anemia (AA) is a blood disorder resulted from over-activated T-cell related hematopoietic failure, with the characterization of hypocellularity and enhanced adipogenic differentiation of mesenchymal stroma cells (MSCs) in bone marrow (BM). However, little is known about the relationship between immune imbalance and polarized adipogenic abnormity of BM microenvironment in this disease entity. In the present study, we differentiated BM-MSCs into osteoblastic or adipogenic lineages to mimic the osteo-adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The increased proportion of CD8 + CD27 + T cells in AA patients is reportedly related to disease severity. CD8 + CD27 + T cells present with a cytotoxic effector phenotype by elevating the proportion of perforin, leading to apoptosis in bone marrow haematopoietic cells 3,16 . Single‐cell RNA sequencing analysis of HSPCs and T cells in AA patients revealed that their CD8 + T cells had a high signal expression related to cell activation and immune response, which may be related to the increase in the number and activation of CD8 + T cells.…”
Section: Aa Is An Autoimmune Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…The increased proportion of CD8 + CD27 + T cells in AA patients is reportedly related to disease severity. CD8 + CD27 + T cells present with a cytotoxic effector phenotype by elevating the proportion of perforin, leading to apoptosis in bone marrow haematopoietic cells 3,16 . Single‐cell RNA sequencing analysis of HSPCs and T cells in AA patients revealed that their CD8 + T cells had a high signal expression related to cell activation and immune response, which may be related to the increase in the number and activation of CD8 + T cells.…”
Section: Aa Is An Autoimmune Diseasementioning
confidence: 99%
“…A pathological T cell-mediated immune response and an imbalanced proportion of immune cells are often observed in patients with AA. [1][2][3] Immunosuppressants can effectively inhibit activated T lymphocytes and promote immune balance to effectively improve haematopoietic function. 4,5 Dendritic cells (DCs) are the most effective antigenpresenting cells (APCs) in the body.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations